(untitled) (Medicine Today, 2013)
Pneumonia is one of the leading causes of morbidity and mortality in under fives throughout the world, particularly in developing countries. A case control study was carried out in Bangabandhu Memorial Hospital, University of Science and Technology during the period of January to July 2006. 192 hospitalized infants of 212 months age group with World Health Organization(WHO) defined severe pneumonia with radiological confirmation were enrolled in the study, while controls were normal infant of same age group attending EPI center for vaccination. The children were managed using a standard protocol, factors were examined by univariate logistic regression analyasis. The factors whose odds ratio were significantly below 25% and considered as medically important were included in multivariate logistic regression analysis. Out of 192 children, 136(70.8%) were male, 56(29.2%) were female, 2-6 months old infants were 120(62.5%), >6 -12 months infants were 72(37.5%), malnutrition were present in 155( 80.72%), 145(75.5%) lived in slum area, 66(33.7%) were treated by quack, 63% were completely immunized and 3(10.5%) died. On multivariate analysis the following risk factors were found significant i.e. malnutrition, indoor smoke resulting from burning wood and manure used as fuel, non immunization, poor economy , poor housing. Significant risk factors for mortality in severe pneumonia are associated with 3rd degree malnutrition and congenital abnormality of heart with Downs syndrome. Malnutrition, indoor smoke, non-immunization, poor economy, poor housing, and smoking in bed room are important risk factors associated significantly with severe pneumonia and fatal outcome was associated with 3rd degree malnutrition. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15901 Medicine Today 2013 Vol.25(1): 9-13